The Escherichia Coli Btue Protein Functions as a Resistance Determinant Against Reactive Oxygen Species - Vasquez-Guzman, C; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Arenas-Salinas, F (2011)
This work shows that the recently described Escherichia coli BtuE peroxidase protects the bacterium against oxidative stress that is generated by tellurite and by other reactive oxygen species elicitors (ROS). Cells lacking btuE (?btuE) displayed higher sensitivity to K2TeO3 and other oxidative stress-generating agents than did the isogenic, parental, wild-type strain. They also exhibited increased levels of cytoplasmic reactive oxygen species, oxidized proteins, thiobarbituric acid reactive substances, and lipoperoxides. E. coli DbtuE that was exposed to tellurite or H2O2 did not show growth changes relative to wild type cells either in aerobic or anaerobic conditions. Nevertheless, the elimination of btuE from cells deficient in catalases/peroxidases (Hpx-) resulted in impaired growth and resistance to these toxicants only in aerobic conditions, suggesting that BtuE is involved in the defense against oxidative damage. Genetic complementation of E. coli ?btuE restored toxicant resistance to levels exhibited by the wild type strain. As expected, btuE overexpression resulted in decreased amounts of oxidative damage products as well as in lower transcriptional levels of the oxidative stress-induced genes ibpA, soxS and katG. © 2011 Arenas et al.